Toward improving uniformity and standardization in the reporting of pancreatic anastomoses: a new classification system by the International Study Group of Pancreatic Surgery (ISGPS) - Shukla, Parul J.; Barreto, Savio G.; Fingerhut, Abe; Bassi, Claudio; Büchler, Markus W.; Dervenis, Christos; Gouma, Dirk J.; Izbicki, Jakob R.; Neoptolemos, John P.; Padbury, Robert; Sarr, Michael G.; Traverso, William; et al. (Surgery, 2010)
Background - To date, there is no uniform and standardized manner of defining pancreatic anastomoses after pancreatic resection. - Methods - A systematic search was performed to determine the various factors, either related to the pancreatic remnant after pancreatic resection or to types of pancreatoenteric anastomoses that have been shown to influence failure rates of pancreatic anastomoses. - Results - Based on the data obtained, we formulated a new classification that incorporates factors related to the pancreatic remnant, such as pancreatic duct size, length of mobilization, and gland texture, as well as factors related to the pancreatoenteric anastomosis, such as the use of pancreatojejunostomy/pancreatogastrostomy; duct-to-mucosa anastomosis; invagination (dunking) of the remnant into the jejunum or stomach; and the use of a stent (internal or external) across the anastomosis. - Conclusion - By creating a standardized classification for recording and reporting of the pancreatoenterostomy, future publications would allow a more objective comparison of outcomes after pancreatic surgery. In addition, use of such a classification might encourage studies evaluating outcomes after specific types of anastomoses in certain clinical situations that could lead to the formulation of best practice guidelines of anastomotic techniques for a particular combination of findings in the pancreatic remnant.
Gesehen am 19.07.2023